2022
DOI: 10.1002/cbf.3690
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, anti‐inflammatory and beneficial metabolic effects of botryosphaeran [(1→3)(1→6)‐β‐d‐glucan] are responsible for its anti‐tumour activity in experimental non‐obese and obese rats bearing Walker‐256 tumours

Abstract: Botryosphaeran, a (1!3)(1!6)-β-D-glucan, presents several beneficial activities, such as antiproliferative, hypoglycemic and antitumoural activities. This study evaluated the effects of botryosphaeran on oxidative stress, inflammation and metabolic activities in Walker-256 tumour-bearing non-obese and obese rats. Wistars rats were divided into four groups: control tumour (CT); control tumour + botryosphaeran (CTB); obese tumour (OT), and obese tumour + botryosphaeran (OTB). In ninth week, obese and non-obese r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(111 reference statements)
0
5
0
Order By: Relevance
“… 40 Yeast β‐glucan has a variety of biological effects, including anti‐inflammatory, immune regulation, and regulation of intestinal flora. 20 , 41 The function of β‐glucan is overall complicated. First, β‐glucan chelates copper ions to alleviate the symptom of AD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 40 Yeast β‐glucan has a variety of biological effects, including anti‐inflammatory, immune regulation, and regulation of intestinal flora. 20 , 41 The function of β‐glucan is overall complicated. First, β‐glucan chelates copper ions to alleviate the symptom of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrate that yeast β‐glucan, the main component of yeast cell wall, is related to the progression of AD 40 . Yeast β‐glucan has a variety of biological effects, including anti‐inflammatory, immune regulation, and regulation of intestinal flora 20,41 . The function of β‐glucan is overall complicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 This EPS consists of a main chain of D-glucose residues linked by β-(1→3) glucosidic bonds, containing approximately 22% side-branch residues at carbon 6, comprising glucose and gentiobiose, 12 and exists in a triple helix conformation. 13 Several studies have demonstrated the biological functions of Botryosphaeran, which have been summarized by Dekker et al 14 Among these functions are anticlastogenic activity, 15 antiproliferative and proapoptotic activity against breast cancer MCF-7 cells (in vitro), 16 hypoglycemic and hypolipidemic activities in diabetic and hyperlipidemic Wistar rats, respectively, 17 anti-obesogenic effect, 10 antioxidant, 18 and antitumor activities in obese and nonobese rats bearing Walker-256 tumor. [19][20][21] These effects were observed in rats and mice on a 15-day period of treatment with Botryosphaeran.…”
mentioning
confidence: 99%